Vous êtes sur la page 1sur 3

Quadratic Expressions (Binomial Products)

Important Formulae

- (a ± b)2 = a2 ± 2ab + b2
2 2 2
( ± ) = ± 2 +

- (a + b)(a b) = a2 b2
2 2
( + ) ( ) =

EXERCISE 1
1. Use the diagram to prove:

(a) (a + b) 2 = a 2 + 2ab + b 2 (b) ( x + p )2 = x 2 + 2 px + p 2

(c) (a b)2 = a 2 2ab + b 2 (d) ( x p ) 2 = x 2 2 px + p 2

(e) (a + b)(a b) = a 2 b 2 (f) ( x + p )( x p) = x 2 p2


2. Use the formula to expand:

(a) ( x + 5)2 = ( + )2 (b) ( x + 10) 2 = ( + )2

Ans: x 2 + 10 x + 25 Ans: x 2 + 20 x + 100

(c) (2 x 5)2 = ( )2 (d) (2 x 3) 2 = ( )2

Ans: 4 x 2 20 x + 25 Ans: 4 x 2 12 x + 9

(e) (2 x + 3 y ) 2 = ( + )2 (f) (3 x 2 y ) 2

Ans: 4 x 2 + 12 xy + 9 y 2 Ans: 9 x 2 12 xy + 4 y 2
2 2
x 2 x y
(g) +y =( + ) (h)
2 2 3

x2 x 2 xy y 2
Ans: + xy + y 2 Ans: + +
4 4 3 9
2 2
3y 4y
(i) 2x + (i) 5x2
4 3

3 xy 9 y 2 40 x 2 y 16 y 2
Ans: 4 x + 2
+ Ans: 25 x +4
+
4 16 3 9
3. Use the formula to expand:

(a) ( x + 2)( x 2) = ( + )( + ) (b) ( x + 5)( x 5) = ( + )( + )

Ans: x 2 4 Ans: x 2 25

(c) (2 x + 3)(2 x 3) = ( + )( + ) (d) (2 x + 3)(2 x 3) = ( + )( + )

Ans: 4 x 2 9 Ans: 4 x 2 9
(e) (2 x + 3 y )(2 x 3 y ) (f) (3 x + 2 y )(3 x 2 y )

Ans: 4 x 2 9 y 2 Ans: 9 x 2 4 y 2
x x x y x y
(g) +y y (h) +
2 2 2 3 2 3

x2 x2 y2
Ans: y2 Ans:
4 4 9
3y 3y 4y 4y
(i) 2x 2x + (j) 5x2 5x2 +
4 4 3 3

9 y2 16 y 2
Ans: 4 x 2 Ans: 25 x 4
16 9
(k) ( x y )( x + y )( x 2 + y 2 )( x 4 + y 4 )

Ans: x8 y8